2001
DOI: 10.1111/j.8755-8920.2001.450502.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory Activity, Biochemistry, and Phylogeny of Ovine Uterine Serpin

Abstract: OvUS inhibits a wide variety of immune responses, including mixed lymphocyte reaction, mitogen-stimulated lymphocyte proliferation, and T cell-dependent antibody production. Recent data have suggested that OvUS functions by inhibiting protein kinase C and interleukin-2-mediated events. OvUS and similar genes present in cattle and pigs diverged from other serpins prior to the divergence of artiodactyls. Since this time, the serpins have apparently undergone adaptive evolution that has led to a conformational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 58 publications
(67 reference statements)
0
16
0
Order By: Relevance
“…Interestingly, the ovine placenta expresses large numbers of aspartic proteinase inhibitor genes, termed pregnancyassociated glycoproteins (31), and the endometrial glands express large amounts of serine protease inhibitors, termed serpins or uterine milk proteins (32), that could regulate the activity of endometrial CTS identified in the present study. Therefore, the molecular control of expression of CTS in the ovine endometrium may play an important role in establishing a regulatory network of multiple proteolytic enzymes responsible for ECM remodeling during implantation and placentation.…”
Section: Discussionmentioning
confidence: 65%
“…Interestingly, the ovine placenta expresses large numbers of aspartic proteinase inhibitor genes, termed pregnancyassociated glycoproteins (31), and the endometrial glands express large amounts of serine protease inhibitors, termed serpins or uterine milk proteins (32), that could regulate the activity of endometrial CTS identified in the present study. Therefore, the molecular control of expression of CTS in the ovine endometrium may play an important role in establishing a regulatory network of multiple proteolytic enzymes responsible for ECM remodeling during implantation and placentation.…”
Section: Discussionmentioning
confidence: 65%
“…The two best-characterized GE secretory products are the ovine uterine milk proteins (UTMP), also termed ovine uterine serpins, and OPN. UTMPs are members of the serpin family of serine protease inhibitors [72] and serve as excellent markers for endometrial secretory capacity during pregnancy in sheep [73][74][75]. In pregnant sheep, UTMP mRNA expression is restricted to GE and not in LE or sGE.…”
Section: Uterine Gland Secretionsmentioning
confidence: 99%
“…UTMP is produced from uterine glandular epithelial cells and is a member of the serpin superfamily of proteinase inhibitors that exhibit weak antiproteinase activity but inhibit a wide range of lymphocyte functions (Ing et al 1989, Peltier & Hansen 2001. Consequently, UTMP is thought to be important in the inhibition of maternal immune responses directed against antigens expressed on the foeto-placental unit (Hansen 2007).…”
Section: Utmp Uterine Serpinmentioning
confidence: 99%